Concerted or Stepwise: How Much Do Free-Energy Landscapes Tell Us about the Mechanisms of Elimination Reactions? - Duarte Gonzalez, F; Gronert, S; Kamerlin, SCL (American Chemical Society, 2014)
The base-catalyzed dehydration of benzene cis-1,2-dihydrodiols is driven by formation of an aromatic product as well as intermediates potentially stabilized by hyperaromaticity. Experiments exhibit surprising shifts in isotope effects, indicating an unusual mechanistic balance on the E2-E1cB continuum. In this study, both 1- and 2-dimensional free energy surfaces are generated for these compounds with various substituents, using density functional theory and a mixed implicit/explicit solvation model. The computational data help unravel hidden intermediates along the reaction coordinate and provide a novel conceptual framework for distinguishing between competing pathways in this and any other system with borderline reaction mechanisms.